2020
DOI: 10.1111/pce.13774
|View full text |Cite
|
Sign up to set email alerts
|

Molecular underpinnings of methyl jasmonate‐induced resistance in Norway spruce

Abstract: In response to various stimuli, plants acquire resistance against pests and/or pathogens. Such acquired or induced resistance allows plants to rapidly adapt to their environment. Spraying the bark of mature Norway spruce (Picea abies) trees with the phytohormone methyl jasmonate (MeJA) enhances resistance to tree-killing bark beetles and their associated phytopathogenic fungi. Analysis of spruce chemical defenses and beetle colonization success suggests that MeJA treatment both directly induces immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 60 publications
5
29
0
Order By: Relevance
“…Indeed, whether an intense and long-lasting induction of defense pathways, a mainly primed defense response, or an intermediate form is optimal, depends on the cost-benefit balance in a given environment [24]. AO-ISR is fundamentally different from SAR, as the trigger is not a necrotizing pathogen, and the phenotype does not depend on salicylic acid but rather on jasmonic acid and ethylene; c) Pseudomonas simiae WCS417-ISR in Arabidopsis [C. M. J. Pieterse, unpublished]: for this IR phenotype nearly all observed defense responses have been shown to be primed and systemically; d) and e) BABA-IR upon application of low and high doses, respectively [22]: low BABA doses lead to systemically primed defense responses, while high BABA doses lead to directly activated responses mainly in the treated plant parts, these two panels clearly illustrate that for one specific IR trigger, the underlying mechanisms can be different; f) Methyl-jasmonate (MeJa)-IR [58][59][60][61][62][63][64]: via direct activation of defense responses [58][59][60][61][62][63] and via priming [62][63][64], MeJa has been described to activate plant resistance both systemically [58,60] as locally [58,59,63].…”
Section: Point 4) An Ecological Assessment Of Fitness-related Costsmentioning
confidence: 99%
“…Indeed, whether an intense and long-lasting induction of defense pathways, a mainly primed defense response, or an intermediate form is optimal, depends on the cost-benefit balance in a given environment [24]. AO-ISR is fundamentally different from SAR, as the trigger is not a necrotizing pathogen, and the phenotype does not depend on salicylic acid but rather on jasmonic acid and ethylene; c) Pseudomonas simiae WCS417-ISR in Arabidopsis [C. M. J. Pieterse, unpublished]: for this IR phenotype nearly all observed defense responses have been shown to be primed and systemically; d) and e) BABA-IR upon application of low and high doses, respectively [22]: low BABA doses lead to systemically primed defense responses, while high BABA doses lead to directly activated responses mainly in the treated plant parts, these two panels clearly illustrate that for one specific IR trigger, the underlying mechanisms can be different; f) Methyl-jasmonate (MeJa)-IR [58][59][60][61][62][63][64]: via direct activation of defense responses [58][59][60][61][62][63] and via priming [62][63][64], MeJa has been described to activate plant resistance both systemically [58,60] as locally [58,59,63].…”
Section: Point 4) An Ecological Assessment Of Fitness-related Costsmentioning
confidence: 99%
“…In Arabidopsis , ISR is dependent on the defence regulatory protein NPR1 but operates independently of SA; 25 instead, ISR typically is based on a priming of JA‐ and ET‐dependent signalling pathways 26,27 . Based on prior discovery of JA as a wound‐responsive defence hormone in plants, 28 JA and its methylated derivative methyl‐jasmonic acid (MeJA) often have been used as chemical IR agents against herbivores and necrotrophic pathogens 29,30 . Moreover, although SAR is predominantly effective against biotrophic pathogens, ISR is more effective against necrotrophic pathogens 31,32 .…”
Section: The Rise and Fall Of Chemical Ir Agentsmentioning
confidence: 99%
“…These results could be explained by a decline in the expression at the time that samples were collected (14 days after elicitation) as described in Milan et al ( 2017 ) or by the suppression of gene expression induced by some metabolites which are produced by the phenylpropanoid pathway, as described in Rubio-Rodríguez et al ( 2021 ). Uncorrelation between terpene metabolite production and the expression of their biosynthesis genes was reported in a MeJA-treated genotype of Norway spruce (Mageroy et al, 2020 ).…”
Section: Discussionmentioning
confidence: 89%
“…Corroborating this, Long et al (2021) reported the requirements of jasmonate signaling for defense responses against Phytophthora nicotianae in tobacco, which included the phenylpropanoid and the sesquiterpenoid biosynthesis pathways. In Norway, spruce accumulation of JA and not SA following wounding of MeJA-treated bark has also been reported (Mageroy et al, 2020) and authors suggest that MeJA primes JA-dependent defenses in the species although they found difficulties to link the response with expression pattern of PR proteins or JA biosynthesis enzymes. We also suggest that the observed increase in JA content could be considered as a marker of the activation of the defense response to the pathogen, since it is common in the three lines tested.…”
Section: Discussionmentioning
confidence: 99%